Preferred Orientation in Nanocomposite Permanent Magnet Materials - 庞利佳 孙光飞 陈菊芳 强文江 黎文安 张锦标 (Journal of rare earths, 2006)
Melt-spun （Nd11.4Fe82.9B5.7）0.99M1 ribbons （M = Zr, Nb, Ga, Zr＋ Ga, Nb ＋ Ga）were prepared by melt-spinning technique. Ga addition is found to be effective for the orientation of c-axis of Nd2Fe14B grains perpendicular to the ribbon plane. Better magnetic properties can be achieved by adding both the two kinds of elements Zr ＋ Ga, Nb ＋ Ga, and it is found that the preferred orientation is further improved. The alignment degree changes with ribbon thickness and is highest when ribbon thickness is 120 μm. Heat treatment can improve the texture degree, but lead to coarser grains. Cryogenic treatment is first applied for the treatment of nanocomposite Nd2Fe14B/α-Fe melt-spun ribbons. The effects on magnetic properties and texture degree of nanocomposite magnets after cryogenic treatment were studied. The result shows that cryogenic treatment is beneficial to the enhancement of texture degree of melt-spun ribbon and the grain size has no obvious change.